Analysis of non-respondent pregnant women who were registered in the Japan Environment and Children's Study: a longitudinal cohort study. Issue 6 (27th June 2019) - Kigawa, Mika; Tsuchida, Akiko; Miura, Kayoko; Ito, Mika; Tanaka, Tomomi; Hamazaki, Kei; Adachi, Yuichi; Saito, Shigeru; Origasa, Hideki; Inadera, Hidekuni
Abstract : Objectives: Non-response to questionnaires in a longitudinal study reduces the effective sample size and introduces bias. We identified the characteristics of non-respondent pregnant women, and compared them with respondents in the Japan Environment and Children's Study (JECS) during the gestational period. Design: This was a questionnaire-based, longitudinal cohort study. Setting: Questionnaires were provided by research coordinators to mothers at prenatal examinations (at obstetrics clinics) or by mail. Mothers were measured twice: during the first trimester and during the second/third trimester. Participants: Data were collected from the 10 129 participating mothers of the 10 288 children surveyed in the 2011 baseline JECS. We excluded responses from mothers who had a miscarriage or stillbirth; therefore, we analysed data from 9649 participants. Primary and secondary outcome measures: Data concerning demographics, medical history, health characteristics, health-related behaviour and environmental exposure were collected via self-administered questionnaires. The response status of participants' partners and contact with their obstetrician were also examined. Multivariate logistic regression analysis was used to examine factors related to non-response. Results: Response was associated with living with one's mother-in-law (ORs: 0.47, 95% CIs: 0.24 to 0.85), positive participation of participants' partner (OR: 0.25, 95% CI: 0.17 to 0.35) and multiple visits to the obstetrician (OR: 0.02, 95% CI: 0.02 to 0.03). Participants who had a medical history of allergic rhinitis, had body pain or drank alcohol had higher odds of responding (ORs: 0.68, 0.96 and 0.36, 95% CIs: 0.48 to 0.95 and 0.95 to 0.98 and 0.16 to 0.72, respectively); those exposed to secondary smoke had lower odds of responding (OR: 1.59, 95% CI: 1.12 to 2.23). Conclusions: The non-response rate decreased when participants reported health-related behaviour or characteristics. Obtaining the understanding of people around each participant might help increase response rates.